The violent offending of drug users: the pathway from childhood maltreatment to violent arrests mediated by conduct disorder and crime age - Guo, Xiao (The journal of forensic psychiatry & psychology, 2022)
The relationship between drug use and violence has a strong empirical basis, with recent studies finding that violent crime of drug users could be due to both drug abuse and pre-existing risk factors like childhood maltreatment and conduct disorder. However, results regarding the mechanism underlying drug use–violence nexus are less consistent. It is unclear how these pre-existing risk factors associate drug use with violent offending. More research exploring mediating factors of the path from childhood maltreatment to violence is in need, especially when drug use variables are included. As such, this study aims to investigate the role of pre-existing risk factor in shaping the drug use–violence association. Data on demographics, drug use, violent offending and pre-existing risk factor were collected between 2018 and 2021 in a sample of housed drug users (N = 202). According to regression analysis results, childhood maltreatment, conduct disorder and onset age of committing crime are predictive of violent arrests of drug users after controlling other covariates. Furthermore, support was found through Structural Equation Modeling analyses for pathways from childhood maltreatment to violent arrests and aggression subsequently mediated by conduct disorder and onset age of committing crime. Limitations and implications are discussed.